Best Proximity Points of MT-Cyclic Contractions with Property UC. (18th May 2020) - Aydi, Hassen; Lakzian, Hosein; Mitrović, Zoran D.; Radenović, Stojan
Abstract: We initiate the notion of generalized M T - cyclic contraction mappings with respect to an auxiliary function φ and investigate the existence of a best proximity point of such mappings in the setting of metric spaces. We also prove the uniqueness of a fixed point, when we assume an additional condition, named as: property UC. Moreover, we discuss the existence and uniqueness of a fixed point of M T -cyclic orbital contractions in the context of ( b -metric) metric spaces.